2021
DOI: 10.1016/j.clml.2021.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Real-World Experience of Axicabtagene Ciloleucel and Tisagenlecleucel for Relapsed or Refractory Aggressive B-cell Lymphomas: A Single-Institution Experience

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…The duration of neurotoxicity was usually short, with median rates between 3 and 14 days (ranging from 1 to 70) ( 36 , 68 , 69 , 75 , 76 , 83 , 85 ). The reversibility of neurotoxic events and the full recovery of ICANS under intensive management were reported in many series ( 9 , 40 , 62 , 67 , 72 , 77 , 85 , 91 ).…”
Section: Icans In Patients With Hematologic Malignancies and Cns Invo...mentioning
confidence: 89%
“…The duration of neurotoxicity was usually short, with median rates between 3 and 14 days (ranging from 1 to 70) ( 36 , 68 , 69 , 75 , 76 , 83 , 85 ). The reversibility of neurotoxic events and the full recovery of ICANS under intensive management were reported in many series ( 9 , 40 , 62 , 67 , 72 , 77 , 85 , 91 ).…”
Section: Icans In Patients With Hematologic Malignancies and Cns Invo...mentioning
confidence: 89%
“…These patients received 19 salvage treatments after CAR T failure, including targeted therapy (10 treatments), immunotherapy (4), chemotherapy (3), or radiation therapy (2). A single-center analysis of 53 patients in the US with relapsed or refractory aggressive B cell lymphomas treated with CAR T between 2017 and 2020 reported that 49% (26/53) of patients were subsequently treated and that post-CAR T progression therapy commonly involved clinical trial enrollment or use of novel agents or supportive care, with no clear standard of care [ 26 ]. A two-center analysis of 34 patients treated with CAR T between 2018 and 2020 in the US found that, among the 12 patients receiving additional salvage therapy, radiotherapy (7/12), polatuzumab/bendamustine/rituximab (3/12) (Pola-BR), and pembrolizumab (3/12) were the most common [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…As each CAR-T-cell therapy reports actual clinical use experience as a class effect, it does not directly compare efficacy or side effects. In another report of Axi-cel (n = 45) and Tisa-cel (n = 8) therapy, the ORR and CR were 79% and 64%, respectively, with a 12-month PFS/OS of 44%/55%; as for adverse reactions, grade ≥3 CRS and ICANS accounted for 6% and 19%, respectively [52]. In a study of 36 Axi-cel-and 13 Tisa-cel-receiving patients, the CR at 100 days after CAR-T-cell infusion was 51%, followed by a six-month PFS and OS of 48% and 71%, respectively; as for adverse reactions, grade ≥3 CRS and ICANS accounted for 10% and 20%, respectively [53].…”
Section: Real-world Evidence Of Clinically Applied Car-t-cell Therapymentioning
confidence: 95%